Osteoarthritis: quantification of the receptor activator of nuclear factor kappa-β ligand (RANKL) in synovial fluid of Thoroughbred horses - De Negri, Luis (2019)
Osteoarthritis (OA) is a disease of great impact that produces functional disability at an early age in racehorses where its diagnosis is usually carried out in advanced stages of the disease. The aim of this study was to demonstrate the presence of the activating receptor ligand of nuclear factor kappa-β (RANKL) in synovial fluid of equines in training. Three healthy horses of two years and four horses of 3-4 years of age with signs of joint inflammation were evaluated clinically and radiographically. Synovial fluid was extracted to quantify the expression of RANKL in different pathological states of the carpus by an ELISA test. The average value of RANKL in healthy horses was 33.13 ± 8.30 pg/ml and in horses with OA signs of 49.03 ± 5.95 pg/ml (p<0.05).